Examining associations between civic engagement and depressive symptoms from adolescence to young adulthood in a national U.S. sample. Issue 2 (3rd April 2019) - Wray-Lake, Laura; Shubert, Jennifer; Lin, Lin; Starr, Lisa R.
ABSTRACT: Many scholars posit that engaging in civic actions enhances mental health, yet existing evidence is limited. To address gaps in the literature and advance understanding of benefits of civic engagement from adolescence to young adulthood, we estimated a longitudinal structural model to test bidirectional associations between civic engagement (i.e., voting, community engagement, political behaviors) and depressive symptoms using nationally representative longitudinal U.S. data. Adolescent and early young adulthood (EYA) depressive symptoms predicted decreases in later voting. Adolescent and EYA community engagement predicted decreases in later depressive symptoms. Analyses suggested that findings generalized across gender, age, socioeconomic status, race/ethnicity, and EYA social roles. Despite key limitations in measurement of civic engagement over time, results provide some support the notion that community engagement may have mental health benefits for youth, and that depression may reduce later civic engagement.